Study of bioactivity, corrosion resistance and fatigue behavior of Ti-12Mo-6Zr-2Fe alloy after different surface treatments - Escobar Claros, Cesar Adolfo (2020)
Demand for new implants with improved bioactivity, corrosion resistance, and optimal mechanical properties has been increasing considerably. In this sense, different surface treatments are applied in titanium alloys to improve their osteointegration process. Nevertheless, the developments of new bioactive surfaces could cause a considerable reduction in fatigue and corrosion strength leading to catastrophic failures in clinical use. For these reasons, this work studied the biocompatibility, corrosion and fatigue performance of Ti-12Mo-6Zr-2Fe alloy treated with three different surface modifications, namely, chemical surface treatment (CST), nanotubes (Nt) and nanopores (NP). Samples were immersed in simulated body fluid (SBF) solution during different periods, 0, 1, 7, and 14 days. After 14 days immersed in SBF, samples with CST showed high hydroxyapatite (HAp) formation; Likewise, samples with Nt and NP exhibited lower and moderated HAP formation, respectively. In samples without surface treatment was not observed HAp formation. The electrochemical behavior was studied through polarization curves and electrochemical impedance spectroscopy (EIS). Samples with Nt and NP displayed higher corrosion resistance and lower passivation current (Ipass) compared with untreated samples, after 14 days of immersion in SBF; samples with CST showed the worst corrosion performance for all the surface conditions studied. Furthermore, within the framework of electrochemical investigations, EIS results of Nt and NP samples showed a characteristic behavior that could not be modeled by traditional equivalent circuits. Thus, it was proposed a two-channel transmission line model for analyzing this impedance results, leading to a successful fitting of the EIS data. Finally, was observed a reduction of the fatigue resistance in the samples treated with NP and CST, associated with hydrogen embrittlement processes, due to the pick-up of hydrogen during the respective surface treatments.